2016
DOI: 10.1177/154431671604000201
|View full text |Cite
|
Sign up to set email alerts
|

Accreditation is Perceived to Improve the Quality of Vascular Testing Facilities

Abstract: Objective Accreditation for noninvasive vascular testing facilities has been available since 1990, but is not mandatory. We sought to determine the perceived value of accreditation among the staff of vascular laboratories accredited by the Intersocietal Accreditation Commission (IAC). Methods A multi-item electronic survey was sent to medical and technical staff and administrative contacts within the IAC database. Respondents were asked to rate statements about the impact of accreditation on their facility. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 9 publications
1
14
0
Order By: Relevance
“…A recent survey by Brinza et al showed that vascular testing facilities find value in accreditation and feel that accreditation had a positive impact on image quality, result reporting, and test performance. 4 The perceptions of these facilities correlate closely with the results of this study demonstrating that the accreditation identifies issues with reporting, image/waveform quality, and protocol which must be corrected before accreditation is granted.…”
Section: Discussionsupporting
confidence: 69%
“…A recent survey by Brinza et al showed that vascular testing facilities find value in accreditation and feel that accreditation had a positive impact on image quality, result reporting, and test performance. 4 The perceptions of these facilities correlate closely with the results of this study demonstrating that the accreditation identifies issues with reporting, image/waveform quality, and protocol which must be corrected before accreditation is granted.…”
Section: Discussionsupporting
confidence: 69%
“…4,12 These findings are consistent with the results of an electronic survey of personnel within IAC-accredited vascular laboratories, where 76% believed that accreditation process helped the facility to identify imaging issues and 70% felt the IAC accreditation process aided in the correction of issues. 13 Furthermore, most laboratories believed IAC accreditation improved report and image quality, 80% and 70%, respectively; two of the most common issues identified in this study.…”
Section: Discussionmentioning
confidence: 76%
“…following the financial crisis (42) . No studies analysing the with health accreditation processes (43) . This study has shown a slight trend towards greater satisfaction perceived with accredited activities as compared with non-accredited ones, in particular with respect to utility, to the methodology used, and to the teaching capacity.…”
Section: Resultsmentioning
confidence: 99%